PENINGKATAN HASIL BELAJAR PANCASILA MENGGUNAKAN MODEL STUDENT TEAMS ACHIEVEMENT DIVISIONS BERBANTUAN CANVA DI KELAS III UPT SDN 27 PASAR KAMBANG KABUPATEN PESISIR SELATAN - Asmaul Husna, Vinanda; Anita, Yesi; Waldi, Atri; Salmaini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was motivated by the low learning outcomes of third-grade students at UPT SDN 27 Pasar Kambang, Pesisir Selatan Regency. This was caused by teacher-centered learning, group activities dominated by high-achieving students, inadequate teaching modules designed by the teacher, and low student motivation to cooperate due to the absence of a reward system. This study aimed to describe the improvement of Pancasila learning outcomes using the Student Teams Achievement Divisions (STAD) model assisted by Canva in third-grade students at UPT SDN 27 Pasar Kambang, Pesisir Selatan Regency. This study was a Classroom Action Research (CAR) using qualitative and quantitative approaches, conducted in two cycles with planning, implementation, observation, and reflection procedures. Data collection techniques included observational analysis, tests, and non-tests. The research subjects were the classroom teacher as observer, the researcher as practitioner, and 22 third-grade students. The results showed that: First, the teaching module in cycle I obtained an average of 87.5% (B), increasing to 100% (SB) in cycle II. Second, teacher activity in cycle I obtained an average of 84.38% (B), increasing to 93.75% (SB) in cycle II. Third, student activity in cycle I obtained an average of 82.81% (B), increasing to 93.75% (SB) in cycle II. Fourth, student learning outcomes in cycle I obtained an average of 78.94 (C), increasing to 87.40 (B) in cycle II. It can be concluded that the STAD model assisted by Canva can improve Pancasila learning outcomes in third-grade students at UPT SDN 27 Pasar Kambang, Pesisir Selatan Regency.